The valiant women - Sabilano, Aura Ancheta (Giraffe Books, 1995)
The book focused on people and events which influenced the valiant women's choice of career profession, vocation or a cause they passionately espouse. Selected names of Filipino women who have touched the lives of others deeply and who have made a difference in their fields of expertise- women's advocacy, fence education, community organizing, gender equality, pediatrics, environmental protection, justice human rights, care for the disable, public health, entrepreneurship, public administration, politics, agrarian reform, literature and business for social progress. All these women went through the proven of "finding your dream." A dream that will need all the love you can give everyday of your life for as long as you live. The author also sought to determine specific contributions of these women to their particular fields of expertise which enable them to make these contributions. Also contains each women's biography, success stories and their pictures.